Theoretical Studies of the CO2 Capture in Atmospheric Gas by Porous Nanoparticles - Vendite, Alexsander Carvalho (2021)
Global warming is a huge threat for life on Earth and requires vast efforts to be tackled. It emerges mostly from the enhanced greenhouse effect, which has major contribution from atmospheric CO2. Multiple procedures must be combined to lessen the impact of global warming, such as emission mitigations, development of environmental friendly technologies and atmospheric carbon capture. The theoretical study of the latter is the target of this work. Specifically, when performed by the metal-organic framework ZIF-8 on CO2, H2O, N2, O2 and Ar under atmospheric conditions. ZIF-8 was considered as a nanoparticle to evaluate how much its surface impacts the gas capture in proportion to the bulk. The surface groups were represented as unsaturated Zn atom, 2-methylimidazole or deprotonated 2-methylimidazole. Those options imply on different values of charge for the ZIF-8 nanoparticle as a whole. The study was heavily structured on molecular simulations, such as Classic Metropolis Monte Carlo, Classic Molecular Dynamics and Born-Oppenheimer Molecular Dynamics. Initially, parametrization of the classic force fields and subsequent validation were performed by electronic structure calculations. Afterwards, O2 and Ar were found to have negligible interaction with ZIF-8. When considering pristine gases with ZIF-8, the absorption was only possible with CO2, while the adsorption was dominated by H2O, followed by CO2, in energetic magnitude order. In the explicit competition between gases, the CO2 absorption was greatly decreased when simulated with either H2O or N2. The CO2 adsorption was mostly unchanged by the presence of N2, while it was inhibited when H2O was available. Also, both CO2 uptake and selectivity were enhanced in lower temperatures and higher pressures. The ZIF-8 nanoparticle with more superficial Zn atoms excelled at capturing CO2. Although it was the nanoparticle with the highest charge, increments of charge made by adding protons to the surface sites had no effect on the CO2 capture. The effectiveness of ZIF-8 nanoparticles to capture CO2 decreased as its size grew. From another perspective, absorbed CO2 was compacted by ZIF-8 similarly to low density liquid CO2. Additionally, adsorbed CO2 was structured in a web that resembled solid phase CO2. Those features highlight the importance of the ZIF-8 surface on the CO2 capture and its potential to store compacted CO2. Along with the specific results of gas capture by ZIF-8, this work also aimed to create guidelines on surface conditions treatment of MOFs.